Prospectiva estratégica, una herramienta para mejorar la competitividad en los Cuerpos de Bomberos del Ecuador - Baño Gamboy, Ángel Rodri (2021)
Global strategic foresight is considered a tool that provides alternatives for planning in a way that organizations can respond to their weaknesses and threats in advance to make them more competitive. The research that is presented had as a general objective: Formulate the strategic prospective for the Fire Departments of Ecuador, which allows them to improve their level of performance in the medium and long term. The methodology was raised from the qualitative paradigm, using the methods of direct observation, the inductive method, and the hermeneutic method of documentary and discourse analysis, its design was documentary, exploratory level, type of descriptive research, as observation units. the collaboration of five (05) chiefs of the fire departments of Ecuador was obtained, through an in-depth interview, with a semi-structured script, as well as documents, files and required bibliographic information. As a result, it was obtained that there is a marked coincidence of the need to establish prospective scenarios that incorporate timely and proactive decisions, more than in emergencies, an update and innovation of the equipment and technology infrastructure, specialized operating processes, expert technical advice. in risks, efficient resource planning, participatory strategic plan, among others. These results motivated the researcher to make a proposal focused on the design of strategic guidelines, based on prospective scenarios to improve the competitiveness and performance of the Ecuadorian fire departments, which was validated by experts in the area.